A Czech version of the Overall Anxiety Severity and Impairment Scale (OASIS): standardization and psychometric properties - Mikoska, Petr; Novak, Lukas; Pilarik, Lubor; Bok, Tomas; Fulep, Martin; Korinek, Richard (BMC psychiatry, 2022)
BACKGROUND: The Overall Anxiety Severity and Impairment Scale (OASIS) is a transdiagnostic measure that assesses severity and impairment associated with anxiety disorders. However, its psychometric properties were primarily examined in English-speaking or western countries. Therefore, this study aims to examine its psychometric parameters in the Czech Republic. METHODS: A large representative sample (n = 1738), a clinical sample (n = 57) and a retest sample (n = 20) were used. In addition to the OASIS, conventional measures of anxiety, depression, personality traits, self-esteem, life satisfaction, and other scales were also administered. Moreover, we examined the latent structure, reliability, validity, and the cut-off score for the Reliable Change Index (RCI) and the Clinically Significant Change Index (CSI). RESULTS: Higher anxiety was found in females, religious non-church members, and students. The Confirmatory Factor Analysis supported the adequate fit of the unidimensional solution: x2(4) = 3.20; p < 0.525; CFI = 1.000; TLI = 1.000;RMSEA = 0, SRMR = 0. The measurement equivalence examination indicated that the OASIS measures anxiety invariantly between males and females. The validity of the OASIS was supported by positive associations with neuroticism, depression, perceived stress, guilt, shame, and the established anxiety measures. The internal consistency was excellent (Cronbach's alpha = 0.96, McDonald's omega = 0.96). The test-retest reliability was acceptable (r = 0.66). The cut-off for the CSI is 6 and the RCI is 5.32. CONCLUSIONS: The OASIS represents a reliable and valid instrument for assessing anxiety in adults. Due to its shortness, excellent psychometric properties, and percentile norms, it is especially useful for short and accurate screening of anxiety and mapping therapeutic changes in clinical practice.
Keywords: Assessment; Psychometrics; OASIS; Measurement; Male; Česká republika; Adult; dospělí; mužské pohlaví; referenční standardy; reprodukovatelnost výsledků; průzkumy a dotazníky; Reproducibility of Results; Czech Republic; úzkost; lidé; psychometrie; ženské pohlaví; Humans; Reference Standards; psychiatrické posuzovací škály; Female; Surveys and Questionnaires; Psychiatric Status Rating Scales; Anxiety